The use and potential commercial development of Athrixia phylicoides - Rampedi, Issac; Olivier, Jana (University of the Free State, 2005)
Athrixia phylicoides (Asteraceae) is a plant indigenous to the north-eastern mountain ranges of South Africa. It has been harvested for generations by rural communities for use as a tea and a medicine as well as to make brooms. Due to the popularity of these products, signs of over-exploitation of the plant have recently been noted. Commercial production of A phylicoides may be considered as a means of alleviating this pressure on the plant’s natural population and its habitat, provided that there is sufficient demand for the plant and its products. This article reports on two surveys conducted to determine the present use of the plant and to assess the demand for its products.

Athrixia phylicoides (Asteraceae) is ’n inheemse plant wat in die noordoostelike bergreekse van Suid-Afrika aangetref word. Die plant word al geslagte lank deur landelike gemeenskappe geoes en vir die maak van tee, medisyne en besems gebruik. Hierdie plantprodukte is baie gewild en dit wil nou voorkom of die plant moontlik oorbenut word. Die kommersiële verbouing van A phylicoides kan oorweeg word as ’n wyse waarop die druk op die natuurlike populasie van hierdie plant asook op sy habitat verlig sou kon word, mits die vraag na die plant en sy produkte groot genoeg is. In hierdie artikel word daar verslag gedoen oor twee opnames wat uitgevoer is om die huidige gebruik van die plant te bepaal en die moontlike vraag na A phylicoides-produkte te beraam.
Keywords: Athrixia phylicoides; Asteraceae; Indigenous plants; Rural and urban areas; Over-exploitation; Commercial production